Pendugaan Cadangan Karbon Pada Tanaman Karet (Hevea brasiliensis Muell. Arg.) Umur 10 Tahun di Perkebunan Rakyat Desa Tarean, Kecamatan Silindak, Kabupaten Serdang Bedagai - Evan Satria Saragih; Muhdi Muhdi; Diana Sofia Hanafiah (Peronema Forestry Science Journal, 2016)
The rate of change in forest area into plantations tend to be greatly improved from year to year. As a result of forest land will be increasingly threatened its existence as it is converted to plantations. For that to know how the ratio of the absorption of CO2 by growers compared with forests. The purpose of this research were to know the carbon content in each section rubber tree (Hevea brasiliensis Muell. Arg.) and to determine the potential of carbon reserves in the rubber tree (Hevea brasiliensis Muell. Arg.) age of 10 years in people plantation Serdang Bedagai. The method of estimaty carbon stocks  had done destructive ends. Selection of plant samples carried out with purposive sampling. The best equation for estimating biomass and carbon selected using allometric equations based on the value of the highest R-Sq and practicality aspect. The results showed that allometric models for biomass and carbon wasW=3.42 DBH1.153 and  C = 0.58 DBH 1,586 respectively. The potential of biomass and carbon in smallholder rubber plantations Tarean Village, District Silindak, Serdang Bedagai were 40.54 tons / ha and 20.58 tons C/ ha ,respectively. Keywords: rubber, Carbon stocks, biomass, allometric models